Синдром Петрушки: роман / Дина Рубина - Рубина Дина Ильинична (Кинообложка, 2015)
Экземпляры: СБ (20191106) / Инвентарный номер: 58572 / Цена: 133.00 / Сис.шифр: Р2 / Авт.знак: Р 82 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6